2022
DOI: 10.1002/jsp2.1237
|View full text |Cite
|
Sign up to set email alerts
|

Modic type 2 changes are fibroinflammatory changes with complement system involvement adjacent to degenerated vertebral endplates

Abstract: Background Vertebral endplate signal intensity changes visualized by magnetic resonance imaging termed Modic changes (MC) are highly prevalent in low back pain patients. Interconvertibility between the three MC subtypes (MC1, MC2, MC3) suggests different pathological stages. Histologically, granulation tissue, fibrosis, and bone marrow edema are signs of inflammation in MC1 and MC2. However, different inflammatory infiltrates and amount of fatty marrow suggest distinct inflammatory processes in MC2. Aims The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…Similarly as in humans, in low‐virulent or early stages of discospondylitis (bacterial discitis and osteomyelitis 43,44 ), MR signal intensity changes in the vertebrae can be encountered that resemble type 1 MCs 45,46 . Damage to the EPs is suggested to facilitate the development of MCs, as it promotes the interaction between IVD tissue and the vertebrae, thereby triggering an autoimmune response 15,28 . Interestingly, a significant association between vertebral EP changes detected on MRI and IVD disease of the adjacent disc was established in dogs, 47 indicating that dogs with IVD disease might also be prone to develop MCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly as in humans, in low‐virulent or early stages of discospondylitis (bacterial discitis and osteomyelitis 43,44 ), MR signal intensity changes in the vertebrae can be encountered that resemble type 1 MCs 45,46 . Damage to the EPs is suggested to facilitate the development of MCs, as it promotes the interaction between IVD tissue and the vertebrae, thereby triggering an autoimmune response 15,28 . Interestingly, a significant association between vertebral EP changes detected on MRI and IVD disease of the adjacent disc was established in dogs, 47 indicating that dogs with IVD disease might also be prone to develop MCs.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 MCs (hyperintense on T1W and T2W) are believed to represent the conversion of normal into fatty bone marrow (together with increased reactive bone and granulation/fibrotic tissue infiltration). Activation of the complement system, an indication for inflammation, has been demonstrated in human MC2 specimens, which has been suggested to be linked to resorption of the disrupted EP 28 . Type 3 MCs (hypointense on T1W and T2W) are believed to represent subchondral bone sclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Still, not all specimens with histopathological changes had MC on MRI. In another human cadaveric study, Heggli et al 125 showed that CEP and BEP damage are strongly associated with MC2. Supporting evidence for CEP damage in MC stems from studies assessing CEP fragments in surgically removed herniated disc tissue at the MC level.…”
Section: Importance Of Cep In Ivd Degenerationmentioning
confidence: 97%
“…120 Areas of vertebral endplate damage may trigger neoinnervation, [120][121][122] with concomitant bone marrow pathologies (MC) also shown to be innervated. 120,[123][124][125] While these sensory fibers generally terminate in or near the endosteal surface of the BEP, the CEP has also been shown…”
Section: Significance In Low Back Painmentioning
confidence: 99%
See 1 more Smart Citation